PERTUMBUHAN POPULASI Daphnia sp. PADA MEDIA BUDIDAYA DENGAN PENAMBAHAN AIR BUANGAN BUDIDAYA IKAN LELE DUMBO (CLARIAS GARIEPINUS BURCHELL, 1822) [Population Growth of Daphnia sp. in A Culture Media With Waste Water of African Catfish (Clarias gariepinus) Intensif Culture] - Darmawan, Jadmiko (BERITA BIOLOGI, 2014)
The accumulation of organic compound from waste feed and feces from intensive catfish culture can give negative impact to the water quality. On the other hand, the need of live feed for freshwater fish larvae are not sufficient. The aim of this research was to study the effectivity of intensively catfish culture wastewater as a media for Daphnia sp. culture. The experimental research design was completely randomized with five treatments, i.e: Using 5 g/l of chicken manure in the media culture of Daphnia as a control while treatments B, C, and D were using wastewater of intensively catfish culture. The concentration of wastewater of intensively catfish culture was 25%, 50%, 75%,and each treatment was replicated four times. Broodstock of Daphnia sp. used at least 1mm diameter with stocking density 20 ind / liter. Data on population growth of Daphnia sp. obtained were processed using analysis of variance with confidence interval of 95%, followed by least significant difference test (LSD). Furthermore, water quality parameters and density of plankton was examined as supporting data. The water quality data was observed every 4 days and plankton density observation was conducted at the beginning and the end of the study. The result of this research showed that the wastewater of an intensive catfish culture could be used as an alternative media for Daphnia sp. culture. Based on the analysis showed that the different media of Daphnia sp. culture significantly influenced to the population growth of Daphnia sp. The most effective media for Daphnia sp. culture in this research was treatment C and D i.e. 75 % and 100% of waste water of intensive catfish culture.